Ambient‐Temperature Sodium–Sulfur Batteries with a Sodiated Nafion Membrane and a Carbon Nanofiber‐Activated Carbon Composite Electrode. Issue 12 (21st April 2015) - Yu, Xingwen; Manthiram, Arumugam
<x xml:space="preserve">Abstract</x> A sodiated Nafion membrane significantly suppresses the polysulfide shuttling and enhances sulfur utilization and cyclability of the room‐temperature Na–S batteries.